KORELASI PERSEPSI KUALITAS ONLINE DENGAN KEPUASAN LAYANAN SISTEM INFORMASI AKADEMIK MAHASISWA DI STMIK SINAR NUSANTARA SURAKARTA - Wahyu Catur Hastuti, Tri Irawati, Wawan Laksito (Jurnal Ilmiah SINUS, 2017)
This research to determine the correlation between the perception of the quality of service satisfaction online with students' academic information system STMIK Sinar Nusantara use today (www.akademik.sinus.ac.id). The population in this study were all students STMIK Sinar Nusantara Surakarta. Total sample of 55 students using a questionnaire to determine the response of students to each variable. Based on the results if the data do content (X1), accurate (X2), format (X3), easy of use (X4), and timeliness (X5) simultaneously or jointly influencing variables Student Satisfaction (Y) and the result is erarti 10.3% of independent variables in this study could affect the dependent variable, while the rest (100% - 10.3% = 89.7%) is explained by other causes beyond the model that are not investigated in this study. Keywords: correlation, online quality, service satisfaction student information system